Produksi Benih Uji Pertumbuhan dan Daya Hasil beberapa Aksesi Jagung Bersari Bebas Unsri J1-J8 pada Lahan Kering Sub-Optimal - E.S. Halimi; M. Hasmeda; P. Amelia; T.P.A. Dewa; I. Pranjaya (xxxx-xxxx, 2020)
Halimi ES, Hasmeda M, Amelia P, Dewa TPA, Pranjaya I. 2020.  Seed production growth and yield evaluation several open-pollinated maize accessions of unsri j1-j8 at sub-optimal dry land. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang  20 Oktober 2020. pp. xx.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Effort to develop open pollinated varieties of maize should be put into a priority to give more benefit to the farmers.  Production of their seeds are also important, since Maize can only be commercially grown from the seeds.  This research was carried out in two-seasons, to produce seeds in 2017/2018  and then planted them for evaluation in 2018/2019 for evaluation.  Research utilized eight Maize accessions called as Unsri-J1 to J8. Research to produce seeds was done by using ear to row method in 3 replication-plots, each consisted of  10 rows with planting distance 75cm x 25 cm.   Research to evaluate growth and yield were done in the field, incorporation with local farmers.  Analysis data were done by using  a randomized block design in nested scheme consisted of 5 plot-samples as blocks. Result of this research indicated that seed production of  Unsri-J1 to J8 in sub-optimal dry land could be done, especially for the Unsri-J1 and J3 accessions that beside showed consintency in growth, also were  able to produce 6.4 and 5.5 ton dry seeds/ha.   Their growth evaluation also showed greater posture and having earlier period of  anthesis, while their yield evaluations, in general, were about equivalent, even more for Unsri-J1 tended to have higher yield than control variety.